"The brain-is wider than the sky-": nature and the sublime American self in Emerson and Whitman - Sheridan, Michael Douglas. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
This thesis̕ primary focus is on the relationship between nature and the development of adistinctly American selfhood, as revealed through the works of Ralph Waldo Emerson andWalt Whitman. The primary framework through which this relationship will be viewed is that of the notion of the Sublime, which over the centuries developed from being a mere rhetoricalmode into being a manner of ontological exploration and discovery. In the work of Emersonand Whitman, this manner became tied up with the then developing idea of a uniquelyAmerican self. This tying-up in turn allowed an oppositional conception concerning the relation of that self to American nature to evolve, and it is this oppositional conception, theway in which it was developed, and its ultimate consequences that this thesis explores.
Keywords: American poetry -- History and criticism.; Sublime, The, in literature.